Caracterização do processo de reparo e dos efeitos da fotobiomodulação em área doadora de enxerto de pele de espessura parcial após queimadura - Carboni, Rosadélia Malheiros (2020)
The objective of the study was to evaluate the comparative effects of photobiomodulation (PBM), using LED and Membracel®, on the reepithelization and wound quality of the skin donor area, in addition to the pain behavior during the wound repair process. Clinical study, with controlled case selection and data collection at the Burn Unit of the General Hospital “Dr. José Pangella ”from Vila Penteado, a public hospital in the city of São Paulo, Brazil. The sample consisted of 21 participants and 25 donor areas, 13 of which were from the control group, which received only conventional treatment (Membracel®) and 12 from the experimental group: Membracel® and LED. Participants were identified by Arabic numbers, according to the order of arrival at the Hospital. The participants' wounds were evaluated in the immediate postoperative period (PO), 1st, 3rd, 5th and 7th postoperative. Quantitative variables were represented by the mean, standard deviation and the median and interquartile range [p25; p75]. The comparison of the distributions of these variables between groups was performed using the Mann-Whitney test. The results showed that there was no difference in the time of re-epithelialization, area and quality of the wound between the groups, however, regarding pain, it was possible to verify, separately in the 5th PO, a significant reduction in the score obtained in the LED group in relation to Membracel. In conclusion, the PBM did not induce changes in the reepithelization period, wound area and wound quality scores of the Bates-Jensen Scale in the evaluated periods, however it induced a reduction in pain compared to the Membracel group.